Analisis Faktor-Faktor yang Berhubungan Dengan Praktik Skrining IMS Oleh Lelaki Seks Lelaki (LSL) Sebagai Upaya Pencegahan Penularan HIV (Studi Kasus Pada Semarang Gaya Community) - Deaselia Carmelita; Zahroh Shaluhiyah; Kusyogo Cahyo; Priyadi Nugraha P. (Jurnal Kesehatan Masyarakat (Undip), 2017)
HIV case distribution in Central Java according to sexes in 2015 revealed Men have higher prevalence 61,5% than women 38,5%. MSM prevalence is increased year by year and believed as the cause of high prevalence HIV in men. STD screening is applied as early detection and prevention in HIV transmission.This study was conducted to analyze factors associated with STD screening implementation in MSM. The method of this study was cross sectional with 96 samples collected with questionaire. Chi square and Rank Spearman was used to analyze the association. This study shows 51% people categorized as good in implementing STD screening. The factors that associated with good implementation of STD screening is the perception about the benefit of STD screening (p-value=0.008), risky sexual behaviour (p-value=0.030), and history of infected by STD (p-value=0.009). Meanwhile, demografic status like age (p=0,688), education level (p=0,427), vocation (p=0,610), marriage status (p=0.415) was not associated with good implementation of STD screening.  Another factor such as knowledge about HIV, STD, and STD screening (p-value=0,602), perception about vulnerability in HIV infection(p-value=0.840), perception in STD severity (p-value=0,467), perception in STD screening accesibilty (p-value=0.780), self motivation in STD screening (p-value=0.467), and condom usage (p-value=0,879) was not associated with good implementation of STD screening by MSM.